Pengaruh karbon aktif sekam padi terhadap penyerapan Pb (timbal) dalam pelumas bekas kendaraan bermotor - Safitri, Rizki Tri; Adhani, Lisa; Nuraliyah, Andi (Institute for Advanced Science Social, and Sustainable Future, 2024)
The number of motorised vehicles, according to the Central Statistics Agency, reached 94,373,324 in 2012, and there was an increase in 2013 to 104,118,986. This is influenced by increasingly rapid population growth and the increasing need for transportation. Used lubricating oil is categorised as B3 waste, which can be seen from its characteristics and its constituent components. Rice husks resulting from milling that are not utilised optimally are usually only used as ash, or the use of rice husks has so far been limited to just being thrown away. Research was carried out regarding the activated carbon test from rice husk waste to adsorb Pb in used lubricating oil using a sulfuric acid activator and determine the effectiveness of reducing Pb (lead). The mass ratio of rice husks before and after calcination is 1:2, where the initial weight of the husks before calcination is 250 grammes to 125 grammes after undergoing calcination. A mass of 10 grammes of adsorbent that has been activated using sulfuric acid and a stirring time of 60 minutes can reduce the lead content of the used lubricant from 49,569 ppm to 39,241 ppm.